1998
DOI: 10.1002/(sici)1099-1352(199812)11:1/6<204::aid-jmr424>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of protein interactions with biosensor technology

Abstract: A methodology using biosensor technology for combined kinetic and thermodynamic analysis of biomolecular interactions is described. Rate and affinity constants are determined with BIAcore. Thermodynamics parameters, changes in free energy, enthalpy and entropy, are evaluated from equilibrium data and by using rate constants and transition state theory. The methodology using van't Hoff theory gives complementary information to microcalorimetry, since only the direct binding is measured with BIAcore whereas micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 19 publications
4
67
0
3
Order By: Relevance
“…The Biacore 3000 extends its utility to the capability of conducting experiments over the temperature range of 4-40°C. By acquiring high-quality data at multiple temperatures it is possible to extract temperature-dependent binding constants on the biosensor [19,32]. It has been previously demonstrated that when the surface plasmon resonance biosensor experiments are performed with care, the equilibrium, thermodynamic, and kinetic constants determined from this surface-based technique match those acquired in solution [19,21,25].…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The Biacore 3000 extends its utility to the capability of conducting experiments over the temperature range of 4-40°C. By acquiring high-quality data at multiple temperatures it is possible to extract temperature-dependent binding constants on the biosensor [19,32]. It has been previously demonstrated that when the surface plasmon resonance biosensor experiments are performed with care, the equilibrium, thermodynamic, and kinetic constants determined from this surface-based technique match those acquired in solution [19,21,25].…”
supporting
confidence: 71%
“…Transition state thermodynamic quantities were determined from the kinetic association (k a ) and dissociation (k d ) rate constants determined as a function of temperature as previously described for similar systems [19,22,24,32]. The linear Eyring equation DG°z ¼ ÀR Ã lnðhk r =k B T Þ ¼ DH°z À T DS°z was applied to the transition state analysis; R is the universal gas constant, h is PlanckÕs constant, k B is the Boltzmann constant, k r is the kinetic association or dissociation rate constant, and all quantities are expressed in reference to standard state conditions.…”
Section: Transition State Data Analysis For Sb-203580mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to determining the interaction affinities and kinetics, thermodynamic analysis of a biomolecular interaction is also possible. This is done by applying van't Hoff's equations to the interaction affinities and kinetics of an interaction obtained at a variety of different temperatures [116,117] 1. the amount of bound analyte, 2. its affinity for the receptor, and 3. the association and dissociation kinetics of the interaction (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4.2 shows the experimental set up and a typical binding curve (sensorgram) from an SPR experiment. The binding curve can then be analysed to determine the kinetic and thermodynamic parameters of the reaction (Roos et al, 1998).…”
Section: ) To Be Conserved In Sm:sx N-terminal Peptide Interaction; Tmentioning
confidence: 99%